PENERAPAN STRATEGI PEMBELAJARAN KONTEKSTUAL (CTL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI MIA MAN 2 MODEL PEKANBARU - Rahayu, Anggia; Holiwarni, Betty; Copriady, Jimmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to increase students learning achievement by implementation of contextual teaching and learning (CTL) strategy on the equilibrium solubility subject in class XI MIA MAN 2 Model Pekanbaru. The type of research is quasy experimental with Randomized Control Group Pretest-Posttest Design. Population consist of 3 class has been tested normality and homogenity using prerequisite data, 2 random samples were selected, XI MIA 1 as experiment class and XI MIA 2 as control class. The experiment class was applied with contextual teaching and learning strategy, while control class without contextual teaching and learning strategy. Instrument in this research is a question of solubility equilibrium that has been test validation and reliability. Results showed instrument is valid and reliable. Data analysis technique is descriptive and inferensy analysis. Hypothesis using Mann Whitney test with significance level (α=0,05), based on the analysis and processing of data obtainable zcount>ztable is 2,27>1,64, its mean implementation of contextual teaching and learning strategy can increase students learning achievement on the on the equilibrium solubility subject in class XI MIA MAN 2 Model Pekanbaru.Key words : equilibrium solubility, learning achievement, contextual teaching and learning strategy